KORELASI KETERAMPILAN MEMBACA PEMAHAMAN CERPEN DENGAN KETERAMPILAN MENULIS TEKS ULASAN CERPEN SISWA KELAS VIII SMP NEGERI 1 PADANG - Satriawan, Rahmad; Basri, Irfani; Abdurrahman, Abdurrahman (Universitas Negeri Padang, 2020)
ABSTRACTÂ The purpose of this study consists of three things as follows. First, it describes the level of reading skills in understanding the short stories of students of class VIII SMP Negeri 1 Padang. Secondly, it describes the level of short story writing skills of students of VIII SMP Negeri 1 Padang. Third, describe the relationship between reading skills understanding short stories and short story writing skills of students of VIII SMP Negeri 1 Padang. The variables of this research are the short story comprehension reading skills as the X variable and the short story writing text writing skills as the Y variable. The research data were the scores of the short story reading comprehension test skills of the eighth grade students of SMP Negeri 1 Padang and the scores of the results of the short story writing skills text review of the eighth grade students of SMP Negeri 1 Padang. The results of this study consisted of three things as follows. First, the reading skills of the short story comprehension of Grade VIII students of SMP Negeri 1 Padang are in the Qualification More Than Enough with an average count of 67.01. Second, the short story writing skills of the eighth grade students of SMP Negeri 1 Padang in short story writing are in the Fair qualifications with an average count of 62.15. Third, based on the results of the t-test, an alternative hypothesis was accepted at the 95% confidence level.Â Kata Kunci: Korelasi, Membaca Pemahaman Cerpen, Menulis Teks Ulasan Cerpen